2015
DOI: 10.1126/scisignal.aaa9432
|View full text |Cite
|
Sign up to set email alerts
|

The insulin response integrates increased TGF-β signaling through Akt-induced enhancement of cell surface delivery of TGF-β receptors

Abstract: Increased activity of transforming growth factor β (TGF-β), which binds to and stimulates cell surface receptors, contributes to cancer progression and fibrosis by driving epithelial cells toward a migratory mesenchymal phenotype and increasing the abundance of extracellular matrix proteins. The abundance of TGF-β receptors at the cell surface determines cellular responsiveness to TGF-β, which is often produced by the same cells that have the receptors, and thus serves as an autocrine signal. We found that Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 112 publications
(171 reference statements)
5
83
2
Order By: Relevance
“…Recycling of TbRI is promoted by interaction with the adaptor CIN85 and is dependent on Rab11-containing recycling vesicles (Yakymovych et al 2015), and recycling of TbRII is promoted by the adaptor protein DAB2 (Penheiter et al 2010). More- over, there appears to exist an intracellular pool of TGF-b receptors (Wu and Derynck 2009), which can be mobilized to presentation at the cell surface by Akt-induced phosphorylation of the endosomal membrane-associated RabGTPase AS160 (Budi et al 2015). Akt is activated by PI3-kinase (e.g., downstream of tyrosine kinase receptors), such as the insulin receptor; thus, activation of such receptors makes cells more susceptible to TGF-b stimulation.…”
Section: Tgf-b Receptor Regulation By Endocytosismentioning
confidence: 99%
“…Recycling of TbRI is promoted by interaction with the adaptor CIN85 and is dependent on Rab11-containing recycling vesicles (Yakymovych et al 2015), and recycling of TbRII is promoted by the adaptor protein DAB2 (Penheiter et al 2010). More- over, there appears to exist an intracellular pool of TGF-b receptors (Wu and Derynck 2009), which can be mobilized to presentation at the cell surface by Akt-induced phosphorylation of the endosomal membrane-associated RabGTPase AS160 (Budi et al 2015). Akt is activated by PI3-kinase (e.g., downstream of tyrosine kinase receptors), such as the insulin receptor; thus, activation of such receptors makes cells more susceptible to TGF-b stimulation.…”
Section: Tgf-b Receptor Regulation By Endocytosismentioning
confidence: 99%
“…Akt-induced phosphorylation of the endosomal membraneassociated Rab-GTPase Akt substrate of 160 kDa (AS160) enhances transportation of the TGFβ receptors from intracellular compartments to the cell surface [91]. AS160 is an active GTPase-activating protein (GAP) for Rab2, Rab8, Rab10, and Rab14 [92], and phosphorylation by Akt inhibits its GAP activity [93].…”
Section: Recyclingmentioning
confidence: 99%
“…A number of talks highlighted how membrane trafficking functions to propagate TGFβ signals. For instance, Rik Derynck (UCSF, San Francisco, USA) showed that most TGFβ receptors reside intracellularly and are transported to the plasma membrane in response to specific stimuli such as high glucose or insulin (Budi et al, 2015;Wu and Derynck, 2009) that induce activation of Akt signaling. Consequently, insulin stimulation greatly enhances the number of TGFβ receptors at the cell surface through an Aktcontrolled transport mechanism, and this increases TGFβ responsiveness while also enabling TGFβ signaling to participate in the response to insulin (Budi et al, 2015).…”
Section: Regulation Of Receptor Trafficking and Turnovermentioning
confidence: 99%
“…For instance, Rik Derynck (UCSF, San Francisco, USA) showed that most TGFβ receptors reside intracellularly and are transported to the plasma membrane in response to specific stimuli such as high glucose or insulin (Budi et al, 2015;Wu and Derynck, 2009) that induce activation of Akt signaling. Consequently, insulin stimulation greatly enhances the number of TGFβ receptors at the cell surface through an Aktcontrolled transport mechanism, and this increases TGFβ responsiveness while also enabling TGFβ signaling to participate in the response to insulin (Budi et al, 2015). Tamara Alliston (UCSF, San Francisco, USA) described how reduced cytoskeletal tension releases TGFβ type I receptors from focal adhesions, enabling them to colocalize with type II receptors to form a functional signaling complex (Rys et al, 2015).…”
Section: Regulation Of Receptor Trafficking and Turnovermentioning
confidence: 99%